2016
DOI: 10.15171/jcs.2016.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of White Noise on Sleep in Patients Admitted to a Coronary Care

Abstract: Introduction: Sleep disorders are a common problem in patients in the critical care unit. The objective of the present study was to determine the effect of white noise on the quality of sleep in patients admitted to the CCU. Methods: The present study was single-blind, quasi-experimental study. A total of 60 patients were selected using the purposive sampling method. Quality of sleep was measured with PSQI on the first day in admission, then after three nights of admission without any intervention for control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Thus, white noise is clearly less damaging to the vasculature within this short time frame compatible with recent observations that white noise can even provide benefit for patients undergoing coronary bypass surgery, probably by masking other annoying and potentially stress-inducing background noise in the coronary care unit. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, white noise is clearly less damaging to the vasculature within this short time frame compatible with recent observations that white noise can even provide benefit for patients undergoing coronary bypass surgery, probably by masking other annoying and potentially stress-inducing background noise in the coronary care unit. 38 …”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that both the arousal index at baseline and during white noise administration were significantly inferior as compared to the night with simulated ICU noise exposure. Similarly, a recent study ( 18 ) showed better scores in the PSQI in 30 ICU patients exposed to broadband sound as compared to another 30 patients who were not. However, the effect of broadband sound in the environmental low noise setting remains unclear.…”
Section: Introductionmentioning
confidence: 61%
“…All participants were interviewed by the researchers, who excluded those with sleep disorders, circadian rhythm problems, psychiatric disorders, and hearing problems, those taking sleep promoting or altering medications, those who were smokers, those who were obese (body mass index >30 kg/m 2 ), and those who were living in a noisy environment. Based on previous studies, the annoyance by outdoor and indoor noise sources was determined by the question, “Thinking about the last 12 months, when you are at home, how much would you say noise from the following sources (road noise, neighbor flat noise, parking noise, airplane noise, commercial noise, and train noise) bothers or annoys you?”[4619] The strength of noise annoyance was rated by the five-step International Commission on Biological Effects of Noise scale of none, slight, moderate, strong, and too extreme. [4619] Those who scored “none” or “slight” were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous studies, the annoyance by outdoor and indoor noise sources was determined by the question, “Thinking about the last 12 months, when you are at home, how much would you say noise from the following sources (road noise, neighbor flat noise, parking noise, airplane noise, commercial noise, and train noise) bothers or annoys you?”[4619] The strength of noise annoyance was rated by the five-step International Commission on Biological Effects of Noise scale of none, slight, moderate, strong, and too extreme. [4619] Those who scored “none” or “slight” were included in the study. In addition, individuals who co-sleep in the same bed or room with another individual or those who attend and take care of others (e.g., parents or children) were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation